LOVE, LOSS, AND LONGING ACROSS POETIC TRADITIONS: A TEXTUAL COMPARISON BETWEEN WESTERN AND EASTERN POETRY - Hikmah Wardani; Iskandar Sulaiman; Fitriyani Fitriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study analyzes the representation of love, loss, and longing in Edgar Allan Poe's "Annabel Lee" and Bai Juyi's "The Song of Everlasting Sorrow" through a comparative literature approach. David Damrosch is used to compare the two poems as works that transcend cultural and historical boundaries. This study uses qualitative methods with a comparative literary analysis approach to the textual elements of both poems. The results show that both poems demonstrate that love, loss, and longing are universal human experiences, but they are represented through different poetic strategies and cultural values. Poe presents personal and romantic emotional expressions, while Bai Juyi connects them to broader historical and social contexts. Keywords: Love, Loss, Longing, Comparative Literature